SOLUSI PEMBIAYAAN UMKM DENGAN PEER TO PEER LENDING SYARIAH (STUDY KASUS PADA PT. AMMANA FINTEK SYARIAH) - Rahadian Firdaus; Achsania Hendratmi (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to determine the application of the concept of Sharia in fintech lending company as an alternative financing of MSMEs in Indonesia by using the principle of Islamic learning stated by Prof. Faturrahman Djamil (2001:249) and quoted by Mardani (2012:91). There are 7 principles of intent in Islam including: The Illahiah Principle, the Principle of Freedom, the Principle of Equality or Equality, the Principle of Justice, the Principle of Compliance, the Principle of Honesty and Truth, and the Written Principle. This study is using the Analytic Network Process (ANP) method which aims to find out the dominant variables in the application of the concept of Shariah peer to peerlending at PT. Ammana Fintek Sharia. The result of this study indicate that three of the seven criterias are namely the Illahiah Principle (23.47%), the Principle of Honesty and Truth (21.44%), the last being the Principle of Compliance (19.44%).Keywords: The Principle of Islamic, Peer to peerLending, MSMEs, Analytic Network ProcessREFFERENCESAli, Zainuddin. 2008. Hukum Ekonomi Syariah. Jakarta: Sinar Grafika.Arner, D.W. 2016. 150 Years of Fintech: An Evolutionary Analysis, JASSA The Fin sia Journal of Applied Finance, Issue: 3, 22-29.Arner, D.W., Barberis, J. dan Buckley, R.P. 2015. The evolution of FinTech: a new post-crisis paradigm?.(No. 2015/047).Ascarya. 2007. Akad dan Produk Bank Syariah. Jakarta: PT RajaGrafindo Persada.Beik, Irfan Syauqi dan Laily Dwi Arsyianti. 2016. Ekonomi Pembangunan Syariah. Jakarta: PT RajaGrafindo Persada.Stern, Caroline, Mikko Makinen dan Zongxin Qian. 2017. FinTechs in China – with a special focus on peer to peer lending, Journal of Chinese Economic and Foreign Trade Studies, Vol. 10 No. 3, pp. 215-228.Dewi, Gemala dkk. 2005. Hukum Perikatan Islam di Indonesia. Jakarta: Kencana.Evers, M. 2012. Main Drivers of Crowd Funding Success: A Conceptual Framework and Empirical Analysis. Master Thesis. Rotterdam School of Management, Erasmus University.Fajar, Mukti. 2016. UMKM di Indonesia Perspektif Hukum Ekonomi. Yogyakarta: Pustaka Pelajar.Haroen, Nasrun. 2007. Fiqh Muamalah. Jakarta: Gaya Media Pratama.Kim, K. 2013. The Experts in the Crowd: The Role of Reputable Investors in a Crowd funding Market.ZEW SEEK Workshop on Social Network Formation and Peer Effects.Mardani. 2012. Fiqh Ekonomi Syariah. Jakarta: Kencana.Milne, Alistair dan Paul Parboteeah. 2016. The Business Models and Economics of Peer-to-Peer Lending. Belgium: European Credit Research Institute.Munawir, A.W. 1984. Kamus  al-Munawir. Yogyakarta: Pondok Pesantren al Munawir.PwC Indonesia. 2019. Indonesia’s Fintech Lending: Driving Economic Growth Through Financial Inclusion.Qardhawi, Yusuf. 1977. Peran Nilai dan Moral dalam Perekonomian Islam. Jakarta: Robbani Press.Rizal, Muhamad dkk. 2018. Fintech As One Of The Financing Solutions For SMEs. Jurnal Pemikiran dan Penelitian Administrasi Bisnis dan Kewirausahaan, Vol.3, No. 2, hal.89-100.Saaty dan Vargas. 2006. Decision Making with The Analytic Network Process Economic, Political, Social and Technological Applications with Benefits, Opportunities, Cost And Risk. New York: Springer Science+Business MediaWahjono, Sentot Imam dkk. (2016). Critical Analysis of Crowdfunding to Finance SMEs in Muslim Countries, Journal Balance, Vol. XIII No. 1.